ENVIRONMENTAL FRIENDLINESS EVALUATION OF GILLNET FISHING GEAR IN MUARA KINTAP VILLAGE, KINTAP SUB-DISTRICT, TANAH LAUT REGENCY - Ramadani, Anisa; Irhamsyah, Irhamsyah; Aminah, Siti; Rosadi, Erwin; Angraeni, Angraeni; Najmuddin, Ahmad; Fadhani, Pangku (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2025)
Gillnets are widely used fishing gears whose environmental impact varies based on their design and application. This study focuses on assessing the environmental friendliness of two types of gillnets—drift gillnets and encircling gillnets—used by artisanal fishermen in Muara Kintap Village, Kintap Subdistrict, Tanah Laut Regency. The research employed a census (total sampling) approach involving 16 respondents from the KUB Putra Pantai fishermen group. Primary data were collected through interviews, observations, and documentation. The environmental friendliness of the fishing gears was assessed using nine criteria derived from the Code of Conduct for Responsible Fisheries (CCRF) by FAO (1995), which include gear selectivity, impact on habitat and biodiversity, catch quality, fisher and consumer safety, by-catch level, involvement of protected species, and social acceptance. Drift gillnets obtained a total score of 28.3, while encircling gillnets scored 26.8. Both are categorized as environmentally friendly fishing gears. The findings show that neither gear type causes habitat damage; both yield good-quality fish, are safe for users and consumers, and are socially accepted. However, both exhibit low selectivity, with Sardinella fimbriata dominating the catch (78.97% for drift gillnets and 88.24% for encircling gillnets). Both drift and encircling gillnets are considered environmentally friendly according to CCRF criteria. Nonetheless, the low selectivity level highlights the need for improvements in gear design and fishing practices to enhance sustainable fisheries management.